Rancang Bangun Aplikasi Interactive Whiteboard Untuk Mendukung Pembelajaran Menggunakan Game Controlling - Yusdianto, Andre; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal JSIKA, 2012)
Learning in the classroom aims to build student knowledge or skill in a particular field of study Learning itself is a process of interaction and communication with educators and learners learning resources in a learning environment. In the process of learning in the classroom between teachers with students certainly needed a media to convey the material of the board. In using these media markers are needed as a tool for writing, eraser board to remove and ink refill for ink on marker. Therefore, to solve problems in the form of learning media do not need to use white board markers, erasers and ink refills, it is proposed to be made ​​of the interactive whiteboard, a large touch screen panel that can function as an ordinary whiteboard or a projector screen computer that can control the images in the computer by touching the surface of the panel without using mouse or keyboard. From research conducted by Steve Kennewel and Alex Morgan 2003, as much as 95% of the students and teachers that are observed in the UK states that interactive whiteboards can add value to learning, although 76% felt that the presence of the interactive whiteboard this would add to their preparation time, like to learn how to operate effectivel. Based on the problems in the areas of learning required and the use of interactive whiteboard technology Nintendo used to replace the function of the board in general, ie write and erase. Keyword: Interactive Whiteboard, Learning Media